Cognitive and affective processes in second language oral communication: a mixed methods research - Portugal-Toro, Arlene; García-Peñalvo, Francisco José; Balderas Ruiz, Luis Antonio; Vences Esparza, Angélica (Frontiers in Education, 2025)
IntroductionThe current global context highlights the development of skills that enable individuals to work together to address common challenges in our society. The interaction of people to try to solve together the situations that concern us all as a society. Knowing how to communicate in English, widely recognized as a lingua franca, is a skill that facilitates effective interaction across diverse contexts. This article presents the results of a study aimed at identifying the relationship between cognitive-affective processes and the achievement of oral communication proficiency in English as a foreign language.MethodsA sample of 53 undergraduate students in elementary education participated in the study. A mixed methods research approach with a concurrent design was employed, utilizing two Likert-scale instruments administered to the entire sample, along with an open-ended questionnaire applied through interviews with a subset of participants. To evaluate the students’ oral communication skills, a semi-structure interview guide was administered and coded according to a Cambridge assessment scale.ResultsThe results indicate that certain cognitive-affective variables are associated with oral communication skills in English: (a) in affective processes, risk-taking and motivation are variables that are highly correlated with oral communication; (b) within cognitive processes, the learning variable shows a strong positive correlation with oral communication; (c) some affective and cognitive variables are positively interrelated, suggesting the importance of studying these factors in conjunction; (d) the qualitative findings both complement and reinforce the quantitative results.DiscussionThis article offers a distinct contribution to English language teaching by integrating multiple variables that influence students’ ability to communicate effectively in English, offering insights that may inform more holistic approaches to developing student’s communicative skills. The findings of this study prove valuable for researchers focusing on English language acquisition and educators seeking effective strategies to help students achieve language proficiency.